Surgery, Complications, and Quality of Life: A Longitudinal Cohort Study Exploring the Role of Psychosocial Factors. Issue 1 (July 2019) - Archer, Stephanie; Pinto, Anna; Vuik, Sabine; Bicknell, Colin; Faiz, Omar; Byrne, Ben; Johnston, Maximilian; Skapinakis, Petros; Athanasiou, Thanos; Vincent, Charles; Darzi, Ara
Abstract : Objective: To determine whether psychosocial factors moderate the relationship between surgical complications and quality of life (QoL). Background: Patients who experience surgical complications have significantly worse postoperative QoL than patients with an uncomplicated recovery. Psychosocial factors, such as coping style and level of social support influence how people deal with stressful events, but it is unclear whether they affect QoL following a surgical complication. These findings can inform the development of appropriate interventions that support patients postoperatively. Methods: This is a longitudinal cohort study; data were collected pre-op, 1 month post-op, 4 months post-op, and 12 months post-op. A total of 785 patients undergoing major elective gastrointestinal, vascular, or cardiothoracic surgery who were recruited from 28 National Health Service sites in England and Scotland took part in the study. Results: Patients who experience major surgical complications report significantly reduced levels of physical and mental QoL ( P < 0.05) but they make a full recovery over time. Findings indicate that a range of psychosocial factors such as the use of humor as a coping style and the level of health care professional support may moderate the impact of surgical complications on QoL. Conclusions: Surgical complications alongside other sociodemographic and psychosocial factors contribute to changes in QoL; the results from this exploratory study suggest that interventions that increase the availability of healthcare professional support and promote more effective coping strategies before surgery may be useful, particularly in the earlier stages of recovery where QoL is most severely compromised. However, these relationships should be further explored in longitudinal studies that include other types of surgery and employ rigorous recruitment and follow-up procedures. Abstract : Supplemental Digital Content is available in the text